2002
DOI: 10.1002/ijc.10433
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of αvβ 3 integrin and disruption of endothelial fibronectin network during the adhesion of the human ovarian adenocarcinoma cell line IGROV1 on the human umbilical vein cell extracellular matrix

Abstract: Key words: extracellular matrix; integrin; ovarian carcinoma; HUVECsNeoangiogenesis is the complex process by which new blood vessels are generated from preexisting vessels. The growth of new blood vessels plays a critical role in a variety of normal physiological events but also in pathological processes. 1 In the case of tumoral angiogenesis, the process is under cell tumor influence and conversely the expansion of solid tumors is critically dependent on vascular networks that provide nutrients for growing t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
20
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 23 publications
3
20
0
Order By: Relevance
“…Thus, the ECM protein-and integrin-mediated Pseudomonas adherence and uptake by A549 cells may be independent from the so-called CFTR innate immunity function [17]. The staining pattern obtained for avb5 integrins in A549 cells was evocative of a localization of these integrins in focal contacts, since they are quite similar to the staining obtained for other integrins in other cell lines [32,33]. The focal contact localization of these integrins strongly suggests that they actively participate in A549 cell behavior as part of functional heterodimers acting as signal transducers [34].…”
Section: Discussionsupporting
confidence: 57%
“…Thus, the ECM protein-and integrin-mediated Pseudomonas adherence and uptake by A549 cells may be independent from the so-called CFTR innate immunity function [17]. The staining pattern obtained for avb5 integrins in A549 cells was evocative of a localization of these integrins in focal contacts, since they are quite similar to the staining obtained for other integrins in other cell lines [32,33]. The focal contact localization of these integrins strongly suggests that they actively participate in A549 cell behavior as part of functional heterodimers acting as signal transducers [34].…”
Section: Discussionsupporting
confidence: 57%
“…An explanation for the reduced invasion of CD13-overexpressing cells might be a decreased adhesion of the cells, which is required for proper invasion in the ECM (Ref. 26; also reviewed by Skubitz (27)]. Because we found only a moderate reduction in adhesion to Matrigel (30% reduction), it is questionable whether this explains the less invasive phenotype.…”
Section: Discussionmentioning
confidence: 69%
“…For instance, integrin αv, β3 is closely related to tumor invasion, metastasis and angiogenesis in ovarian cancer, malignant melanoma, breast cancer and prostate cancer [13]. Numerous studies have confirmed that integrin αv plays an important role in ovarian cancer progression and metastasis [1417]. By activating integrin-linked kinase (IL-K), the integrin αv subunit promotes growth and proliferation of ovarian cancer cells, and mediates their adhesion and migration [18].…”
Section: Discussionmentioning
confidence: 99%